SOCIAL INNOVATION AND COLLABORATIVE GOVERNANCE FOR MSME DEVELOPMENT:A CONCEPTUAL FRAMEWORK FOR INCLUSIVE LOCAL ECONOMIC RESILIENCE - Raden Roro Fatmasari; Anggun Yolistina (Organisasi Kreatif Indonesia Emas, 2024)
Background: MSME development is often approached through isolated interventions such as training, finance, digitalization, or market promotion. These interventions can be useful, but persistent local economic problems frequently require coordination among entrepreneurs, community organizations, government, educational institutions, financial actors, and private partners. Social innovation and collaborative governance provide complementary perspectives for designing such coordination. Aims: This article develops an integrative conceptual framework explaining how social innovation and collaborative governance can strengthen MSME capability, inclusion, and local economic resilience. Research Method: The study uses an integrative conceptual review of established literature on social innovation, collaborative governance, public value, entrepreneurial ecosystems, social capital, and community-based enterprise. No primary survey, interview, experimental, or statistical data are claimed. Results and Conclusion: The synthesis identifies five connected mechanisms: shared problem definition, inclusive stakeholder participation, co-creation of solutions, institutional coordination, and adaptive learning. Social innovation contributes new responses to unmet needs, while collaborative governance provides processes through which diverse actors can build trust, allocate responsibilities, and sustain implementation. The framework also identifies risks of symbolic participation, elite capture, fragmented accountability, and project dependence. Contribution: The paper proposes a Social Innovation-Collaborative Governance Framework for MSME development and provides propositions, governance principles, and practical indicators for future empirical testing.